Hotels in Medan During the Colonial Era - Yinka Ronatama Tarigan; Mia Maya Sari; Raudotul Jannah; Ammar Zhafran Ryanto (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to examine the role of hotels in Medan during the colonial period, not only as places of accommodation but also as centers of social and cultural activities. The research uses a qualitative method with a content analysis approach, intended to draw conclusions based on historical data while considering the socio-cultural context of the time. The findings reveal that colonial-era hotels in Medan played a significant role in social life, serving as venues for gatherings, parties, and events attended by various elite groups such as colonial officials, entrepreneurs, and community leaders. Although many of these hotels no longer exist, their architectural and historical legacy continues to influence the development of the hospitality industry in Medan today.